Properties of High Strength Self-Compacting Concrete Containing Waste Glass - Azra (My University, 2024)
The glass manufacturing industry generates a significant amount of waste glass as a by-product of its industrial processes. The management and disposal of this substance present a significant environmental concern, so it is strongly suggested to explore suitable alternatives. Furthermore, the expense associated with the excavation of natural sand, coupled with its limited supply and the growing need for it, has compelled the concrete industry to seek out cost-effective and readily accessible substitutes. An environmentally conscious approach is necessary to both save the environment and safeguard natural resources simultaneously. Utilizing waste glass as a substitute for sand in concrete is a practical choice for advancing sustainable development. The purpose of the current research work is to design high strength self-compacting concrete (HSSCC) mixes incorporating waste glass as fine aggregate replacement. The range of HSSCC mixes were designed to have strength lying in between 80-100 MPa at 28 days. Waste glass was varied from 0 to 100% as sand substitution material; whereas steel fibers proportions were taken as 0.25 and 0.5% to design HSSCC mixes. The fresh properties included the slump flow, L-box, sieve segregation resistance of HSSCC. The strength properties included the compressive strength, splitting tensile strength, Modulus of elasticity and non-destructive testing include rebound hammer and ultrasonic pulse velocity. The durability properties included the water absorption, sorptivity, Alkali silica reaction and surface electrical resistivity of HSSCC made with waste glass. The strength and durability properties of HSSCC were performed and analysed for upto 90 days. The microstructural analysis included Scanning electron microscopy (SEM), Energy dispersive spectroscopy (EDS) and X-ray diffraction (XRD) of HSSCC mixes at all ages of curing. Test results demonstrated that all the mixes completely complied with the classifications specified in the European code. The addition of waste glass significantly increased the filling ability, passing ability and sieve segregation resistance of HSSCC mixes. Compressive strength of HSSCC mixes upto 100% waste glass exhibited lower results when compared to a concrete mix consisting solely of 100% sand. The strength of HSSCC mixes showed a positive correlation with the duration of the process of curing. The compressive strength of HSSCC mixes containing 25%, 50%, 75% and 100% waste glass was found to be 8.12%, 11.1%, 14.4%, 27.61% lower, respectively than the control mix (93.27 MPa) at 28 days. It was also estimated that due to addition of 0.25% steel fibers in waste glass 25%, 50%, 75% and 100%, there was v decrease in compressive strength of concrete by 9.14%, 12.89%, 14.43%, 31.15% in comparison to the control HSSCC mix (98.3 MPa) and also for addition of 0.5% of steel fiber in 25%, 50%, 75%, 100% of waste glass, there is decrease in compressive strength by 6.51%, 11.5%, 17.6%, 28.23% in comparison to the control mix (95.58 MPa). The splitting tensile strength of HSSCC mixes exhibited an downwards trend as the waste glass concentration was raised from 0 to 100%. Additionally, splitting tensile strength also improved with longer curing periods. The splitting tensile strength increased at 7, 28 and 90 days when steels fibers were added. Modulus of elasticity also decreased due to addition of waste glass. There was gradual decrease in rebound number in 28 days and with ultrasonic pulse velocity no pattern was obtained due to fibers and there was decrease in value due to waste glass. HSSCC mixtures upto 100% waste glass showed a decrease in water absorption and the size of permeable gaps. Utilizing waste glass in HSSCC mixes at a maximum of 100% waste glass resulted in decreased sorptivity values for upto 28 days. Due to Alkali silica reaction (ASR), there was expansion of mortar bars due to waste glass. Electrical resistivity was also increased due to increase in glass content. SEM study of HSSCC containing upto 100% waste glass revealed the development of calcium silicate hydrate layers, resulting in a more compact and uniform structure of the concrete matrix.
Keywords: Self Compacting; Waste glass; Glass Manufacturing